2021
DOI: 10.1142/s0219477521500516
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Impact of Chinese Treasury Bond Futures on the Information Content of IRS

Abstract: This paper investigates the impact of Chinese Treasury bond (CTB) futures on the information content of interest rate swap (IRS) from a multifractality perspective. We first use multifractal detrended fluctuation analysis (MF-DFA) method and show that the swap rate and the CTB yield exhibit strong multifractality. In addition, employing multifractal detrended cross-correlation analysis (MF-DCCA) method, we find that cross-correlations between the swap rate and the CTB yield are multifractally persistent. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…When the borrower has credit problems, the bank can consider increasing interest rate discounts for such customers to reduce credit risk and improve bank income. ird, the financial market is developing toward diversification; correspondingly, S Bank can hedge through financial derivatives such as exchange options and interest rate futures to realize the effective control of housing credit risk [30][31][32].…”
Section: Improving the Construction Of Bank Risk Assessmentmentioning
confidence: 99%
“…When the borrower has credit problems, the bank can consider increasing interest rate discounts for such customers to reduce credit risk and improve bank income. ird, the financial market is developing toward diversification; correspondingly, S Bank can hedge through financial derivatives such as exchange options and interest rate futures to realize the effective control of housing credit risk [30][31][32].…”
Section: Improving the Construction Of Bank Risk Assessmentmentioning
confidence: 99%
“…The econophysics literature has investigated multifractal cross-correlations in various financial markets. Examples of these research areas include the stock market [30,31], crude oil [32,33], cryptocurrencies [34][35][36], energy market [37,38], bond market [39], precious metals [40], and green bonds [41].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that China's new energy market is not efficient and has multifractal cross-correlations with other markets. Furthermore, Yang et al [39] provided additional evidence of the multifractality of financial markets by studying the treasury bond market in China. On the commodity market side, Wang et al [40] demonstrated multifractality in the Chinese Rebar market using asymmetric MFDCCA, revealing complex structures.…”
Section: Introductionmentioning
confidence: 99%